HOW DOES ISLAM SUPPORT THE GREEN ECONOMY? A STUDY ON TURATH PERSPECTIVE - Mirzal, Husnul; Zaki, Irham; Zusak, M Bastomi Fahri (Bank Indonesia, 2024)
This study addresses how Islam supports a green economy using a thematic analysis of the turath. The results show that Islam strongly supports the implementation of the green economy. The green economy has been a part of Islamic teachings long before its conception in this modern era. In Islam, there are the four main goals of the green economy, namely creating an economy that is inclusive and fair, environmentally friendly, resources sustainable, and resources efficient. Islam can provide guidance and for solutions to all human problems, including those related to the economy and environment. As a policy recommendation, the Government and related parties can leverage on a religious approach to develop a green economy by for examples including Islamic values as well as involving Islamic institutions and Islamic figures in the National Green Economy Development Roadmap such that its goals can be better achieved.